Design of metamaterial leaky‐wave antenna with continuous beam scanning capability for sensing applications. Issue 9 (27th May 2022) - Zhang, Hao; Liu, Hongtao; Xu, Shugong; Yang, Guangli; Luo, Yong
Abstract: We report the fundamental design guideline for a metamaterial (MTM) leaky‐wave antenna with continuous tuning capability of radiation directions without causing band gaps. The proposed design is the composite right–left hand (CRLH) type MTM, and each cell has a slot that could be in the open‐ or close‐state with indicating as 0 and 1 states. With the MTM‐based design, a leaky‐wave antenna consisting of eight MTM units can be controlled by states of periodical MTM units such as coding states 0000–0000, 1010–1010, …, 1111–1111, rather than by frequency tuning, thereby realizing continuously beam scanning without any stopband from −30° to +30° in the fixed frequencies from 9 to 9.2 GHz. The proof‐of‐concept level tuning capability is confirmed by experiments using the closed‐ or open‐patches that emulate the electrical short‐ or open‐state of individual switch. The measured results show that the MTM‐based leaky‐wave antenna can obtain state‐dependent and continuous beam scanning at the fixed frequencies of 9–9.2 GHz. It can be applied for radar sensing with requiring continuous and state‐dependent beam scanning properties.